Transient Modeling and Simulation of Variable Geometry Industrial Gas Turbines - HASHMI, MUHAMMAD BAQIR (2020)
Gas Turbines are widely used in the power industry and petrochemical industries. The present thesis deals with transient modeling and simulation of industrial gas turbines featured by a schedule for variable inlet guide vanes (VIGV). Both the modelling (steady-state and transient) and simulation are carried out by using a commercial software called GasTurb 12 that was originally developed by Dr Kurzke. The whole process is demonstrated by considering a three-shaft industrial gas turbine (GE LM1600) because it deals with a lot of complexities during transient operation. First, the design point and off-design steady state results were compared with data from already published literature. Secondly, the combined effect of performance deterioration phenomena (VIGV, compressor fouling, and high inlet air temperatures) on the overall health and performance of gas turbine was investigated through a steady state off-design simulation. Thirdly, the transient simulation is performed to study load change phenomena through acceleration and deceleration; two kinds of fuel flow schedules were incorporated.